Separated : Family and Community in the Aftermath of an Immigration Raid - Lopez, William D., 1982- (Book collections on Project MUSE., 2019)
"Through extensive ethnographic study of the aftermath of an ICE raid in one Latino community in Michigan, the author details the incredible strain that it placed on the community, the families, and the individuals left behind. Lopez's case study reveals the public health impacts of ICE raids on stable immigrant communities in the heartland of the country"--